Strategi bank syariah dalam mendukung pembiayaan ramah lingkungan melalui skema Green Financing - Daris, Daris (Maliki Interdisciplinary Journal, 2025)
Green financing is a crucial instrument for promoting sustainable development within the Islamic banking sector. Islamic banks play a strategic role in ensuring that financing activities are not solely profit-oriented but also contribute positively to environmental preservation. This study aims to analyze the strategies of Islamic banks in supporting environmentally friendly financing through green financing schemes. The research employs a literature review method by examining various academic sources related to green finance practices in Indonesia. The findings reveal that green financing strategies include product innovation such as green sukuk and eco-murabahah, the enhancement of sustainable financial literacy, and the reinforcement of internal policies aligned with Environmental, Social, and Governance (ESG) principles. Furthermore, collaboration between regulators, financial institutions, and the public is essential to expanding green financing implementation. In conclusion, the adoption of green financing not only strengthens the competitiveness of Islamic banks but also reflects the essence of maqashid syariah by promoting welfare, justice, and environmental sustainability.